2010
DOI: 10.5539/ass.v6n4p122
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Buddy Support System Implementation among Science Teachers: The Case of Malaysia

Abstract: The biggest challenge that is being faced by the Malaysian Education scenario occurred when shifting of the Malaysia's National Science Curriculum from the use of Malay language to English as the medium of instruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…This is particularly informative to current online educational settings where a one-on-one pair-learning system operates. Although the buddy system has been proven in terms of its effectiveness to motivate people to learn and help people master materials in offline settings (e.g., Abdullah et al, 2010;Thomson, 2010), it might not function in the same way in an online setting where a large group of users share materials and help each other. Instead of the traditional way of pairing two users as exclusive buddies, an in-group-based team assignment might effectively encourage learners to contribute more to the group in the context of an online learning community (Levine & Crowther, 2008).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…This is particularly informative to current online educational settings where a one-on-one pair-learning system operates. Although the buddy system has been proven in terms of its effectiveness to motivate people to learn and help people master materials in offline settings (e.g., Abdullah et al, 2010;Thomson, 2010), it might not function in the same way in an online setting where a large group of users share materials and help each other. Instead of the traditional way of pairing two users as exclusive buddies, an in-group-based team assignment might effectively encourage learners to contribute more to the group in the context of an online learning community (Levine & Crowther, 2008).…”
Section: Resultsmentioning
confidence: 98%
“…Outside the online realm, studies have identified three different types of buddies -mentor (Abdullah, Alzaidiyeen, & Seedee, 2010), helper (Damon, 1984;Thomson, 2010), and supporter (Bauld, Bell, McCullough, Richardson, & Greaves, 2009;Holland, Everitt, Johnson, & Devi, 2008;May & West, 2000) -depending on the interactant's goals and the buddy's qualifications to assist the interactant to achieve those goals. Therefore, the buddy's role centers on the interactant's needs to optimize a counterpart's satisfaction with the specific support that s/he needs (Curtrona, 1990;Curtrona, Russell, & Rose, 1986).…”
Section: Online Buddy As a Solutionmentioning
confidence: 99%
“…Previous research pointed out the benefits of parent involvement not only towards the students but also give benefit to the school and parents schools and parents. This is keep up by Asli cited in Abdullah (2011) mentioned that parental involvement in children's education progress as a prime aspect for the children, family and school relationship bestow to the children's education (Abdullah, 2011) and (Zakaria, et al, 2013). Parent involvement and parent participation are the similar terms because this is referring to the parent actions (Selvam, 2013).…”
Section: Literature Reviewmentioning
confidence: 92%
“…According to Henderson and Mapp cited in Georgiou and Tourva (2007) parental involvement has been defined as different behaviors and practices of parents at school and home, this is including parent's aspirations, expectations, attitudes and opinions towards their child's education. As mentioned by Abdullah (2011) parental involvement refer to the parent's variation of activities at home as well as at school where it is positively influences the children education.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the PPSMI exercise, the Ministry of Education Malaysia and the States' Education Departments has distributed a large sum of allocations from their annual spending towards training of teachers nationwide (A. Abdullah, Alzaidiyeen, & Seedee, 2010). Furthermore, expensive state-of-the-art CDs were produced alongside printed materials, requiring the use of laptops, LCDs and installation of special screens in the classrooms, most of which was foreign to the teachers.…”
Section: English In Malaysia: a Case Of Schism Between Planning And Imentioning
confidence: 99%